Neuroprotective effects of zerumbone on cognitive functions: a scoping review - Farah Syahibah Mohd Hariri; Asmah Hamid; Farah Wahida Ibrahim; Nurul Farhana Jufri; Mazlyzam Abdul Latif; Khairana Husain (Penerbit Universiti Kebangsaan Malaysia, 2026)
Zerumbone (ZER) is a sesquiterpenoid compound derived from the rhizome of Zingiber zerumbet (L.) Smith, also known as Lempoyang ginger. Evidence suggests that ZER may help manage cognitive disorders. Its unique chemical structure and effects on the central nervous system make it a promising candidate for treating neurodegenerative diseases. This review analyzes nine preclinical studies, including six rodent and three cell-based models, which demonstrate ZER’s neuroprotective properties. The studies show that ZER has strong anti-inflammatory and antioxidant effects, with six out of nine reporting increased antioxidant enzyme activity. Other mechanisms include cholinesterase inhibition, stimulation of neural stem cell proliferation, and regulation of key signalling pathways. ZER’s lipophilic nature allows it to cross the blood–brain barrier and act within the central nervous system. In all six animal studies, ZER improved behavioral and cognitive outcomes in models of Alzheimer’s disease, vascular dementia, scopolamine-induced amnesia, and age related cognitive decline. These results support further development of ZER as a natural therapeutic for neurodegenerative diseases and cognitive impairment. However, additional research, especially well-designed clinical trials, is needed to confirm its safety and efficacy in humans.